Critical perspectives on social control and social regulation in Canada - Daschuk, Mitch; Brooks, Carolyn; Popham, James F. (Fernwood Publishing, 2020)
"How does social regulation shape who is 'deviant' and who is 'normal'? Critical Perspectives on Social Control and Social Regulation in Canada is an introduction to the sociology of what has traditionally been called deviance and conformity. This book shifts the focus from individuals labelled deviant to the political and economic processes that shape marginalization, power and exclusion. Class, gender, race and sexuality are the bases for understanding deviance, and it is within these relations of power that the labels 'deviant' and 'normal' are socially developed and the behaviours of those less powerful become regulated. This textbook introduces readers to theories and critiques of traditional approaches to deviance and conformity. Using vivid and timely examples of contemporary social regulation and control, this textbook brings to life how forces of social control and marginalization interact with social media, sex work, immigration, anti-colonialism, digital surveillance and social movements, and much more. Theories and critiques are clarified with summaries, definitions, rich illustrative examples, discussion questions, recommended resources and test banks for instructors."--